Concurrent Infection With the Filarial Helminth Litomosoides sigmodontis Attenuates or Worsens Influenza A Virus Pathogenesis in a Stage-Dependent Manner - Hardisty, Gareth R.; Knipper, Johanna A.; Fulton, Alison; Hopkins, John; Dutia, Bernadette M.; Taylor, Matthew D. (Frontiers in Immunology, 2022)
Filarial helminths infect approximately 120 million people worldwide initiating a type 2 immune response in the host. Influenza A viruses stimulate a virulent type 1 pro-inflammatory immune response that in some individuals can cause uncontrolled immunopathology and fatality. Although coinfection with filariasis and influenza is a common occurrence, the impact of filarial infection on respiratory viral infection is unknown. The aim of this study was to determine the impact of pre-existing filarial infection on concurrent infection with influenza A virus. A murine model of co-infection was established using the filarial helminth Litomosoides sigmodontis and the H1N1 (A/WSN/33) influenza A virus (IAV). Co-infection was performed at 3 different stages of L. sigmodontis infection (larval, juvenile adult, and patency), and the impact of co-infection was determined by IAV induced weight loss and clinical signs, quantification of viral titres, and helminth counts. Significant alterations of IAV pathogenesis, dependent upon stage of infection, was observed on co-infection with L. sigmodontis. Larval stage L. sigmodontis infection alleviated clinical signs of IAV co-infection, whilst more established juvenile adult infection also significantly delayed weight loss. Viral titres remained unaltered at either infection stage. In contrast, patent L. sigmdodontis infection led to a reversal of age-related resistance to IAV infection, significantly increasing weight loss and clinical signs of infection as well as increasing IAV titre. These data demonstrate that the progression of influenza infection can be ameliorated or worsened by pre-existing filarial infection, with the outcome dependent upon the stage of filarial infection.